Pro PHP Application Performance: Tuning PHP Web Projects for Maximum Performance - Padilla, Armando (Apress, 2012)
The book is separated into two general sections, the front end and back end of a web application. The first part of the book covers the front end, helping you identify bottlenecks the browser encounters during rendering and how to remove these bottlenecks. This initial section also covers the use of PHP best coding practices and how to apply caching using the many tools available. The second part of the book covers the back end, teaching you about the many types of web server software, how to optimize the software, and tips on optimizing your database.